RISIKO PENDAPATAN PADA USAHATANI JERUK SIAM DI KABUPATEN SAMBAS - Any Suryantini, Dewi Kurniati, Slamet Hartono, Sri Widodo, (Jurnal Social Economic of Agriculture, 2014)
This study aims to determine the income, income risk and the factors that affecting the income risk of citrus farming in Sambas district. The data used in this study is the cross sectional from 106 farmers in Sambas district. Analysis of the data using the formula of farm income, coefficient of variation and residual squared of income function model. The result showed that the value of average income of citrus farming per hectare per year is Rp 18,492,410 million. Variability of the average value at income risk of citrus farmers is 0.809 or 80.9%. The variable that decreases the income risk is managerial capabilities while the variables which increases the income risk of citrus farming are size farm and the price of NPK fertilizer.   Keywords: Risk, Income, Citrus Farming